SCHOOL-BASED MANAGEMENT AS A METHOD TO IMPROVE EDUCATION QUALITY IN SENIOR HIGH SCHOOLS: A PERSPECTIVE ON THE HEADMASTER'S ROLES - Firman, Muhammad; Berliana, Berliana; Warta, Waska (Paedagogia: Jurnal Pendidikan, 2024)
This research is motivated by the crucial role of school principals in school management and the enhancement of education quality, particularly within the framework of School-Based Management (SBM). The significance of this study is underscored by the substantial impact of education on a nation's development and the pivotal role played by school principals in achieving optimal educational quality. The primary objective of this research is to explore the involvement of school principals in implementing SBM at SMA Negeri 1 Sukaraja, Sukabumi Regency, and assess the impact of their leadership on educational quality improvement. The theoretical foundation of this study rests on the concepts of School-Based Management (SBM) and the theory of school principal leadership. Employing a qualitative approach with a single case study design, the research seeks to provide insights into the successful implementation of the SBM approach by the headmaster of SMA Negeri 1 Sukaraja. This implementation involves active participation from parents, teachers, students, and the local community in the decision-making process, reflecting a more democratic and inclusive management style in school administration. Despite the evident success, the study also uncovers challenges faced in this implementation, including resistance to change and constraints in resources.